Promoting community health through preventive medicine - Bendebka, Ramzi; Shogar, Ibrahim; Fettane, Amar (IIUM PRESS, 2019)
This study aims to highlight the potential role of physicians and healthcare providers in promoting health within the community, especially using preventive medicine. Preventive medicine is defined as practices used to prevent diseases. Doctors have a unique place within the community based on respect and trust. Most often, doctors think of patients as individuals who present themselves differently to doctors in clinics and hospitals. But, in terms of public health, the community is the patient, and doctors can treat the whole community using preventive medicine. In addition, doctors have a role in determining the general policy on health services, and they can use their position to influence and push different groups within the community to utilise beneficial health care policies and promote health conditions to the various segments of society. Accordingly, the application of the preventive medicine model is instrumental in promoting health within the community, can help doctors understand different health issues, monitor improvements in health status indicators and reduce disparities within the community. All of these goals are fully consistent with the philosophy of Islam through the general purposes, which emphasize on the protection of life, mind and wealth, which are preserved only through the rationalization of public health behaviour and the provision of distinctive medical services, help to preserve the human element and intellect and maintain its existence. Moreover, it can reduce public expenditures that often burden countries and weaken the fabric of society.